Plateaus, Multiplicities, and Interconnections in Distant Star: Between Complexity and Rhizomes - Guarín, Daniel (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article analyzes the narrative structure of the novel Distant Star, by Roberto Bolaño, from the theory of complexity and from the philosophical concept of Rhizome. The stories of the novel are understood as plateaus that are connected like rhizomes or that interact in a complex system to give meaning to the work. The article begins with a synthesis of the story, then relates the concepts of complexity and rhizome, and finally presents the plateaus and interconnections created by Bolaño in the novel. It is concluded that Distant Star can be read in a linear way, following the trail of the antagonist; or in a rhizomic way, without beginning or end, but with a variety of plateaus, intertextualities and stories that are slightly connected. Wieder becomes a point without end, and like the novel, a rhizome in the universe of Bolaño's work.